Plexiform schwannoma in the maxillary alveolar ridge: a case report - Bueno, Marcus Vinícius; Duarte, Anna Carolina Coelho; Sinhorini, Patrícia Anaya; Carvalho, Tayná Mendes Inácio de; Machado, Gustavo Grothe; Ceccheti, Marcelo Minharro; Zambon, Camila Eduarda (Journal of Oral Diagnosis, 2021)
Schwannomas are benign tumors of the peripheral nerve sheath originating from Schwann cells, which can manifest in head and neck regions and are rare in the oral cavity, especially their involvement in the maxillary alveolar ridge, which is even more atypical. Among all its variants, plexiform schwannoma is characterized by an intraneural multinodular growth. Its differential diagnosis of plexiform neurofibroma is justified by the fact that the latter is pathognomonic for neurofibromatosis and carries great risks of malignancy. In this paper, we present a rare clinical case report of a plexiform schwannoma in a gingival alveolar ridge in a 33-year-old male patient, in which we describe his clinical, histopathological, immunohistochemical aspects and his due approach which, after incisional biopsy diagnosed with plexiform schwannoma, was approached for excision of the lesion by the maxillofacial surgery of Hospital das Cínicas, University of São Paulo Medical School, as well as their respective 7, 14 and 30 day postoperative periods, no signs of recurrence so far. Therefore, in these cases, we emphasize the importance of a thorough clinical examination and the need for additional tests, such as histopathological and immunohistochemical analyzes to determine the correct diagnosis and promote the appropriate treatment.